Safety, Tolerability, Pharmacokinetics, and Drug Interaction Potential of SPR741, an Intravenous Potentiator, after Single and Multiple Ascending Doses and When Combined with β-Lactam Antibiotics in Healthy Subjects - Eckburg, Paul B.; Lister, Troy; Walpole, Susannah; Keutzer, Tim; Utley, Luke; Tomayko, John; Kopp, Ellen; Farinola, Nicholas; Coleman, Scott (Antimicrobial agents and chemotherapy, 2019)
SPR741 is a novel polymyxin B derivative, with minimal intrinsic antibacterial activity and reduced nonclinical nephrotoxicity compared to levels with polymyxin B, that interacts with the outer membrane of Gram-negative bacteria, enhancing penetration of coadministered antibiotics. SPR741 is a novel polymyxin B derivative, with minimal intrinsic antibacterial activity and reduced nonclinical nephrotoxicity compared to levels with polymyxin B, that interacts with the outer membrane of Gram-negative bacteria, enhancing penetration of coadministered antibiotics. The safety, tolerability, and pharmacokinetics (PK) of SPR741 were evaluated in two studies, after single and multiple intravenous (i.v.) doses in healthy adult subjects and after coadministration with partner antibiotics. In the single and multiple ascending-dose study, SPR741 or placebo was administered as a 1-h infusion at single doses of 5 to 800 mg and in multiple doses of 50 to 600 mg every 8 h (q8h) for 14 days. In the drug-drug interaction study, a single 400-mg i.v. dose of SPR741 was administered alone and in combination with piperacillin-tazobactam, ceftazidime, and aztreonam. PK parameters for SPR741 and partner antibiotics were determined using noncompartmental analysis. After single doses, a dose-linear and proportional increase in mean maximum concentration in plasma ( C max ) and area under the concentration-time curve (AUC) was observed. At doses of 100 to 800 mg, >50% of the dose was excreted in the urine in the first 4 h postdose. After multiple doses, the mean half-life was 2.2 h on day 1 and up to 14.0 h on day 14, with no evidence of accumulation after 14 days of dosing up to 400 mg. The PK profile of SPR741 and partner antibiotics was unchanged with coadministration. SPR741 was generally well tolerated at doses up to 1,800 mg/day. These data support further clinical development of SPR741 for treating serious infections due to resistant bacteria. (These studies have been registered at ClinicalTrials.gov under identifiers NCT03022175 and NCT03376529.)